Biomarker triterpenoids of Centella asiatica as potential antidepressant agents: Combining in vivo and in silico studies - Mando, Zaynab; Mando, Huda; Afzan, Adlin; Shaari, Khozirah; Hassan, Zurina; Mohamad Taib, Mohamad Nurul Azmi; Zakaria, Fauziahanim (Elsevier, 2024)
Although there are various treatments available for depression, some patients may experience resistance to treatment or encounter adverse effects. Centella asiatica (C. asiatica) is an ancient medicinal herb used in Ayurvedic medicine for its rejuvenating, neuroprotective and psychoactive properties. This study aims to explore the antidepressant-like effects of the major constituents found in C. asiatica, i.e., asiatic acid, asiaticoside, madecassic acid, and madecassoside at three doses (1.25, 2.5, and 5 mg/kg, i.p), on the behavioural and cortisol level of unpredictable chronic stress (UCS) zebrafish model. Based on the findings from the behavioural study, the cortisol levels in the zebrafish body after treatment with the two most effective compounds were measured using enzyme-linked immunosorbent assay (ELISA). Furthermore, a molecular docking study was conducted to predict the inhibitory impact of the triterpenoid compounds on serotonin reuptake. The in vivo results indicate that madecassoside (1.25, 2.5, and 5 mg/kg), asiaticoside and asiatic acid (5 mg/kg) activated locomotor behaviour. Madecassoside at all tested doses and asiaticoside at 2.5 and 5 mg/kg significantly decreased cortisol levels compared to the stressed group, indicating the potential regulation effect of madecassoside and asiaticoside on the hypothalamic-pituitary-adrenal axis overactivity. This study highlights the potential benefits of madecassoside and asiaticoside in alleviating depressive symptoms through their positive effects on behaviour and the hypothalamic-pituitary-adrenal (HPA)- axis in a chronic unpredictable stress zebrafish model. Furthermore, the in silico study provided additional evidence to support these findings. These promising results suggest that C. asiatica may be a valuable and cost-effective therapeutic option for depression, and further research should be conducted to explore its potential benefits.